In the shadow of a people's president - Cooray, Evans (Colombo Vijitha Yapa Publications, 2008)
On life and times of former Sri Lankan president R. Premadasa, 1924-1993; autobiographical account of Evans Cooray, former press secretary to the Sri Lankan president.
Age Group: Adult
Keywords: Cooray, Evans; Premadasa, R., 1924-; Presidents -- Sri Lanka -- Biography; Sri Lanka -- Politics and Government -- 1978